(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Folklore is the oral history of a culture’s customs, including music, storytelling, history, folklore, and myths, passed down through generations. Recognizing the familiarity of folklore in everyday life. This research starts with creating Folklore-based teaching materials using the 4D research design (Define, Design, Develop, and Disseminate). Data is gathered through many methods, including literature review, classroom observations, interviews, and questionnaire distribution. This study collected data in the field using observation sheets, interviews, field notes, and questionnaires to get user responses.